2021
DOI: 10.1186/s13068-021-02069-8
|View full text |Cite
|
Sign up to set email alerts
|

Cellulosic ethanol production by consortia of Scheffersomyces stipitis and engineered Zymomonas mobilis

Abstract: Background As one of the clean and sustainable energies, lignocellulosic ethanol has achieved much attention around the world. The production of lignocellulosic ethanol does not compete with people for food, while the consumption of ethanol could contribute to the carbon dioxide emission reduction. However, the simultaneous transformation of glucose and xylose to ethanol is one of the key technologies for attaining cost-efficient lignocellulosic ethanol production at an industrial scale. Geneti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Despite that the ethanol yield of 8b-S38 in 100 g/L xylose media was lower than that of AD50 strain (Additional file 2 : Table S2), its yield in mixed-sugar media was comparable with AD50 (96%) [ 30 ] in mixed sugars, with 97.58% in G2X10 and 92.85% in G2X15 media (Additional file 2 : Table S3). Strain FR2 was another newly engineered strain for efficient xylose fermentation with another copy of xylAB and talB - tktA inserted in the genome of parental strain 8b and its ethanol yield in the mixed-sugar media was 95.5% [ 41 ]. Interestingly, another engineered strain FR1 was also constructed in that work with only talB - tktA inserted in 8b, but showed no difference to the parental strain.…”
Section: Resultsmentioning
confidence: 99%
“…Despite that the ethanol yield of 8b-S38 in 100 g/L xylose media was lower than that of AD50 strain (Additional file 2 : Table S2), its yield in mixed-sugar media was comparable with AD50 (96%) [ 30 ] in mixed sugars, with 97.58% in G2X10 and 92.85% in G2X15 media (Additional file 2 : Table S3). Strain FR2 was another newly engineered strain for efficient xylose fermentation with another copy of xylAB and talB - tktA inserted in the genome of parental strain 8b and its ethanol yield in the mixed-sugar media was 95.5% [ 41 ]. Interestingly, another engineered strain FR1 was also constructed in that work with only talB - tktA inserted in 8b, but showed no difference to the parental strain.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a co-culture of cellulolytic At and ethanolgenic Clostridium thermolacticum achieved enhanced ethanol yield, which is 80% of the theoretical maximum during cellulose fermentation [ 51 ]. Another study showed that a co-culture of A. thermocellum and Thermoanaerobacter pseudethanolicus is effective for improved ethanol production during batch fermentation [ 52 , 53 ]. Here, we proposed a CBP strategy by employing a co-culture of At and Ts ( Figure 4 ), in which lignocellulose biomass can be synergetically hydrolyzed by both cellulase systems of At and Ts, and cellobiose and cellodextrins are produced from cellulose and can be utilized directly by both At and Ts while hemicellulose-derived pentoses can be only utilized by Ts.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, enzyme‐catalyzed degradation has been widely used because of its low cost and environmental friendliness, which can overcome the shortcomings of other degradation methods (e. g., chemical and physical methods), including corrosiveness to the reactor, harsh reaction conditions, formation of by‐products, and so on [16] . Even lignocellulose can be hydrolyzed directly by microorganisms, but all involve enzyme systems [17] . Moreover, the premise of efficient use of enzymes in LCB degradation is to solve the challenges like high cost of enzyme degradation, and long reaction cycle.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Even lignocellulose can be hydrolyzed directly by microorganisms, but all involve enzyme systems. [17] Moreover, the premise of efficient use of enzymes in LCB degradation is to solve the challenges like high cost of enzyme degradation, and long reaction cycle.…”
Section: Introductionmentioning
confidence: 99%